An observational study of associations among maternal fluids during parturition, neonatal output, and breastfed newborn weight loss - Gibb William; Peterson Wendy E; Woodend A Kirsten; Noel-Weiss Joy; Groll Dianne L (BMC, 2011)
Abstract Background Newborn weight measurements are used as a key indicator of breastfeeding adequacy. The purpose of this study was to explore non-feeding factors that might be related to newborn weight loss. The relationship between the intravenous fluids women receive during parturition (the act of giving birth, including time in labour or prior to a caesarean section) and their newborn's weight loss during the first 72 hours postpartum was the primary interest. Methods In this observational cohort study, we collected data about maternal oral and IV fluids during labour or before a caesarean section. Participants (n = 109) weighed their newborns every 12 hours for the first three days then daily to Day 14, and they weighed neonatal output (voids and stools) for three days. Results At 60 hours (nadir), mean newborn weight loss was 6.57% (SD 2.51; n = 96, range 1.83-13.06%). When groups, based on maternal fluids, were compared (≤1200 mls [n = 21] versus > 1200 [n = 53]), newborns lost 5.51% versus 6.93% (p = 0.03), respectively. For the first 24 hours, bivariate analyses show positive relationships between a) neonatal output and percentage of newborn weight lost (r(96) = 0.493, p < 0.001); and b) maternal IV fluids (final 2 hours) and neonatal output (r(42) = 0.383, p = 0.012). At 72 hours, there was a positive correlation between grams of weight lost and all maternal fluids (r(75) = 0.309, p = 0.007). Conclusions Timing and amounts of maternal IV fluids appear correlated to neonatal output and newborn weight loss. Neonates appear to experience diuresis and correct their fluid status in the first 24 hours. We recommend a measurement at 24 hours, instead of birth weight, for baseline when assessing weight change. Because practices can differ between maternity settings, we further suggest that clinicians should collect and analyze data from dyads in their care to determine an optimal baseline measurement.